Antennal sensory organs of Scathophaga stercoraria (Linnaeus, 1758) (Diptera: Scathophagidae): ultramorphology and phylogenetic implications - Liu, Xian-Hui; Liu, Jia-Jia; Li, Xin-Yu; Zhang, Dong (Zootaxa, 2016)
Scathophaga stercoraria (Linnaeus, 1758) is a well-established insect model species involved in numerous investigations on behavior, biology, phylogeny, genetics and evolution. The antennal sensilla of S. stercoraria are examined via scanning electron microscopy in order to emphasize their importance on taxonomy and phylogeny. On antennal scape and pedicel, both microtrichiae and several sharp-tipped mechanoreceptors are observed, while another two structures, setiferous plaques and pedicellar button, are also detected on antennal pedicel. One type of sensory pit and four types of antennal sensilla, including trichoid sensilla, basiconic sensilla, coeloconic sensilla and clavate sensilla, are observed on antennal funiculus. Similarity and disparity of setiferous plaques among different calyptrate groups are analyzed in terms of phylogeny. The phylogenetic results supported by morphology of setiferous plaques strongly accord with the cladistic relations based on known molecular tree, implying the potential taxonomic and phylogenetic implications of the plaques in Calyptratae.